STUDY OF THE IMPLEMENTATION OF A VOIP WITH A PABX IN A WLAN NETWORK - MAKI MUGENYI , Daniel S; MWIRA WAYESU , Daniel; BABONANGENDA BINZIMUNGU , Jimmy; ENGANGE PILIPILI , Syntiche (Revue Internationale du Chercheur, 2025)
Abstract This article discusses the integration of a VoIP telephony system, coupled with an IP PBX, into a corporate WLAN network (the case of Lagrace.net in the DRC). It highlights the technical and economic advantages of such a solution in terms of cost reduction, improved communication quality, and simplified management, relying in particular on the Zoiper tool and the Elastix server, without an Internet connection. The implementation study of a VOIP (Voice Over IP) solution with a PBX (Private Automatic Branch Exchange) in a WLAN (Wireless Local Area Network) involves analyzing the integration of IP telephony into a wireless infrastructure. The process involves several technical and organizational steps to ensure smooth and reliable voice communication. This implementation study aims to effectively integrate VoIP and a PABX into a WLAN network, allowing information to circulate and be processed across all departments of an IT administration while ensuring optimal performance, good security, and simplified management, particularly for long-distance and international calls, by using the Internet rather than traditional telephone lines.